A review of recent advances in histopathological assessment of head and neck squamous cell carcinoma. (22nd August 2019) - Chegini, Soudeh; Mitsimponas, Konstantinos; Shakib, Kaveh
Abstract: Squamous cell carcinoma (SCC) is the most common non‐cutaneous head and neck (H&N) malignancy. Referrals for suspected SCC are seen by oral and maxillofacial surgery (OMFS) surgeons and represent the bulk of 2‐week wait referrals. The diagnosis and treatment of SCC is heavily influenced by national and international guidelines. The majority of research and funding is directed towards this condition. This has led to continuous changes to update these guidelines. However, there remain areas of controversy and conflicting evidence. This article summarises articles pertinent to pathologists between 2016 and 2018 published in the leading British OMFS journal. A total of 22 published articles relating to the histopathology of non‐cutaneous H&N SCC were selected.